Tezepelumab in severe asthma: chest computed tomography assessment of airway remodeling and clinical remission - Lupia, Chiara; Battaglia, Caterina; Pastore, Daniela; Lee, Youngjin; Piazzetta, Giovanna Lucia; Chiarella, Emanuela; Lobello, Nadia; Sireno, Giovanni; Pullano, Alessandro; Crimi, Claudia; Vatrella, Alessandro; Manti, Francesco; et al. (Frontiers in Pharmacology, 2026)
IntroductionSevere asthma is characterized by persistent uncontrolled symptoms despite optimal standard therapy and/or by the need for high-intensity treatment to maintain control. Thymic stromal lymphopoietin (TSLP) is a key innate cytokine that promotes bronchial inflammation in both T2-high and T2-low asthma, thus representing a suitable therapeutic target. Tezepelumab, a human monoclonal antibody designed to block TSLP, has been shown to be able to dampen airway inflammation and improve patients’ symptoms and overall outcomes.MethodsThis study evaluated the effectiveness of tezepelumab in patients with severe asthma in a real-world clinical setting, examining its capacity to induce clinical remission and improve radiological markers of disease. Twenty patients with severe uncontrolled asthma received subcutaneous tezepelumab at a dose of 210 mg every 4 weeks. Clinical, functional, biologic, and radiological data were collected at baseline and after 12 months of treatment.ResultsThe results showed a significant increase in Asthma Control Test (ACT) score, from baseline 11.70 ± 1.78 to 20.15 ± 1.38 (p < 0.0001). Oral corticosteroid (OCS) intake decreased from 12.50 mg/day (5.00–25.00) to 0.00 mg/day (0.00–3.75) (p < 0.0001), and the rate of yearly exacerbations lowered from 2.0 (2.0–3.0) to 0.0 (0.0–1.0) (p < 0.0001). There was also a notable increase in pre-bronchodilator forced expiratory volume in 1 s (FEV1), from baseline 57.15% ± 17.18% to 66.35% ± 18.09% (p < 0.001). Clinical remission was achieved by 30% of patients, while 55% reached partial remission. Radiologically, the Mucus Plug Score (MPS) decreased from 5.36 ± 2.85 to 3.94 ± 2.69 (p < 0.0001), and radiological metrics showed inverse correlations with functional parameters. In simple logistic regression analysis, lower MPS values at baseline and at follow-up were significantly associated with higher odds of achieving complete clinical remission at 12 months of add-on tezepelumab therapy.ConclusionIn summary, tezepelumab induced significant benefits in patients with severe asthma in this real-world cohort, improving symptoms, lung function, and radiological outcomes.